Innovation In The Development Of Islamic Religious Education With A Multicultural Approach - Parnawi, Afi; Idris , Abdullah; Zufriyatun, Zufriyatun; Rafiqi, Rafiqi (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to describe the innovation in the development of Islamic religious education with a multicultural approach in Mantang Housing, Sagulung Village, Sagulung Sub-district, Batam City. The innovation is designed to create an educational environment that is inclusive, values diversity and promotes intercultural tolerance. The methods used involve multicultural curriculum design, multicultural-based extracurricular activities, teacher training, local community involvement, technology utilization, problem-based learning approaches, and measurement and evaluation. Through this approach, a broader understanding of Islamic teachings is expected, while promoting respect for cultural diversity in society. Periodic evaluations are conducted to assess the effectiveness of the program and identify areas of improvement to achieve the goal of inclusiveness and tolerance in Islamic religious education in Mantang Housing.